International Network of "Teachers of indigenous peoples, rural Africans and Afro-descendants of the Universidad Pedagógica y Tecnológica de Colombia - Varios, Varios (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
International Network of "Teachers of indigenous peoples, rural Africans and Afro-descendants of the Universidad Pedagógica y Tecnológica de Colombia